Chick and quail specific pattern of endplates and fibre-types in the plantaris muscle - Grim, M; Christ, B; Jacob, H J; Vrabcová, M (Physiologia Bohemoslovaca, 1985)
Species-specific endplate distribution and fibre-type pattern were found in the plantaris muscle (PL) of the chick and quail. The PL is proposed as a model for studies of nerve-muscle interactions in chimeras.
Keywords: Species Specificity; Muscles; křepelky a křepelovití; Foot; Neuromuscular Junction; kur domácí; Animals; druhová specificita; Quail; nervosvalová ploténka; noha (od hlezna dolů); zvířata; Chickens; nervosvalové spojení; Motor Endplate; svaly